Comparison of Prediction Rules and Clinician Suspicion for Identifying Children With Clinically Important Brain Injuries After Blunt Head Trauma. (20th April 2016) - Atabaki, Shireen M.; Hoyle, John D.; Schunk, Jeff E.; Monroe, David J.; Alpern, Elizabeth R.; Quayle, Kimberly S.; Glass, Todd F.; Badawy, Mohamed K.; Miskin, Michelle; Schalick, Walton O.; Dayan, Peter S.; Holmes, James F.; et al.
Abstract: Objective: Children with minor head trauma frequently present to emergency departments (EDs). Identifying those with traumatic brain injuries (TBIs) can be difficult, and it is unknown whether clinical prediction rules outperform clinician suspicion. Our primary objective was to compare the test characteristics of the Pediatric Emergency Care Applied Research Network (PECARN) TBI prediction rules to clinician suspicion for identifying children with clinically important TBIs (ciTBIs) after minor blunt head trauma. Our secondary objective was to determine the reasons for obtaining computed tomography (CT) scans when clinical suspicion of ciTBI was low. Methods: This was a planned secondary analysis of a previously conducted observational cohort study conducted in PECARN to derive and validate clinical prediction rules for ciTBI among children with minor blunt head trauma in 25 PECARN EDs. Clinicians recorded their suspicion of ciTBI before CT as <1, 1–5, 6–10, 11–50, or >50%. We defined ciTBI as 1) death from TBI, 2) neurosurgery, 3) intubation for more than 24 hours for TBI, or 4) hospital admission of 2 nights or more associated with TBI on CT. To avoid overfitting of the prediction rules, we performed comparisons of the prediction rules and clinician suspicion on the validation group only. On the validation group, we compared the test accuracies of clinician suspicion > 1% versus having at least one predictor in the PECARN TBI age‐specific prediction rules for identifying children with ciTBIs (one rule for children <2 years [preverbal], the other rule for children >2 years [verbal]). Results: In the parent study, we enrolled 8, 627 children to validate the prediction rules, after enrolling 33, 785 children to derive the prediction rules. In the validation group, clinician suspicion of ciTBI was recorded in 8, 496/8, 627 (98.5%) patients, and 87 (1.0%) had ciTBIs. CT scans were obtained in 2, 857 (33.6%) patients in the validation group for whom clinician suspicion of ciTBI was recorded, including 2, 099/7, 688 (27.3%) of those with clinician suspicion of ciTBI of <1% and 758/808 (93.8%) of those with clinician suspicion >1%. The PECARN prediction rules were significantly more sensitive than clinician suspicion >1% of ciTBI for preverbal (100% [95% confidence interval CI = 86.3% to 100%] vs. 60.0% [95% CI = 38.7% to 78.9%]) and verbal children (96.8% [95% CI = 88.8% to 99.6%] vs. 64.5% [95% CI = 51.3% to 76.3%]). Prediction rule specificity, however, was lower than clinician suspicion >1% for preverbal children (53.6% [95% CI = 51.5% to 55.7%] vs. 92.4% [95% CI = 91.2% to 93.5%]) and verbal children (58.2% [95% CI = 56.9% to 59.4%] vs. 90.6% [95% CI = 89.8% to 91.3%]). Of the 7, 688 patients in the validation group with clinician suspicion recorded as <1%, CTs were nevertheless obtained in 2, 099 (27.3%). Three of 16 (18.8%) patients undergoing neurosurgery had clinician suspicion of ciTBI <1%. Conclusions: The PECARN TBI prediction rules had substantially greater sensitivity, but lower specificity, than clinician suspicion of ciTBI for children with minor blunt head trauma. Because CT ordering did not follow clinician suspicion of <1%, these prediction rules can augment clinician judgment and help obviate CT ordering for children at very low risk of ciTBI.